National security, journalism, and law in an age of information warfare - Ambinder, Marc; Henrichsen, Jennifer R.; Rosati, Connie (The Oxford series in ethics, national security, and the rule of law, 2024)
'National Security, Journalism, and Law in an Age of Information Warfare' helps one understand how secret-keepers, journalists, and sources are navigating unprecedented challenges in an age when trust in government and traditional media is low and the spread of disinformation through social media undermines efforts to inform and protect the public